Analisis Faktor Perubahan Gaya Hidup Gen Z di Wilayah Jakarta dalam Memanfaatkan Fasilitas Fitness Center Menggunakan Grounded Theory - Wicaksono, Muhammad Haston Samudra; Putri, Juandela Herina; Oktarini, Dwi Indah; Heikal, Jerry (PT. Media Akademik Publisher, 2024)
Currently, there are plenty of changes in Gen Z lifestyle trends regarding the use of fitness center facilities in the Jakarta area. Based on this phenomenon, this research was carried out to find out the influential changes in Gen Z's lifestyle at fitness center facilities, with the limitation of research conducted at 6 fitness centers in the Jakarta area. This study used a qualitative method with a grounded theory approach. Data collection was carried out using the one-on-one interview method, with a sample of respondents selected based on snowball sampling. The results showed that the coding scheme consisted of 28 codes, which formed 9 categories and depicted 3 themes consisting of ideal body shaping, enhancing body health, and external factors, with a total frequency of 32 points. The most influential factor in Gen Z's lifestyle change is the motivation to improve body fitness, with 16 points as the highest frequency in coding.